Miniaturized reconfigurable metamaterial based bandstop filter for wireless applications - Chavda, Khyati; K. Sarvaiya, Ashish; K. Vala, Mehul (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
The design of compact size and high efficiency metamaterial based reconfigurable microstrip bandstop filter for IEEE 802.11 WLAN applications is developed. This paper presents a switchable dual-mode filter, it resonant at 2.4 GHz and 3.6 GHz. The hexagonal metamaterial resonator inserted switch as PIN diode which form reconfigurable filter. By changing the DC bias of the diode, the filter can be reconfigured with a controlled precision, resulting in the frequency reconfigurable. The CST simulator used to simulate filter design, measuring a return loss over -29.12 dB and a low insertion loss less than -0.2 dB, which is a great performance. The filter is compact at the size of 8 mm×12 mm×1.6 mm design using Rogers RT Duroid 5880 substrate.